1964
DOI: 10.1063/1.1726008
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evidence for Localized Excitons in the Spectra of Charge-Transfer Complex Molecular Crystals

Abstract: The polarized absorption and emission of the anthracene—TNB complex crystal are shown to provide evidence for localization of low-energy excitation in this crystal. The absorption and fluorescence polarization ratios at 300°K are very different (5.6:1 and about 15:1, ‖c: ⊥c on 110) the former being close to an oriented gas value. The latter corresponds to a charge-transfer complex more closely aligned with the c axis of the crystal. The motion of the excited molecule is in accord with the behavior of a dipole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1966
1966
1997
1997

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Before going on with the detailed discussion, we have to mention whether the excited state is delocalized over many or several D and A moieties in the crystals as an exciton or localized on one D−A pair. Hochstrasser et al and Haarer et al considered that CT excited states of molecular crystals of weak D−A complexes are rather localized (self-trapped), because of its alternating molecular stacks, strong electron−phonon coupling, and also an appreciable Coulomb interaction between generated highly ionic component molecules. , Recently, we compared the transient absorption spectrum of a 1:1 CT crystal of durene−PMDA and that of 10 -3 M PMDA-doped durene crystal and found good agreement between the spectra . Here, we have further diluted PMDA to 10 -4 M in the durene crystal, but its transient absorption spectrum was still in accordance with that of the 1:1 CT crystal.…”
Section: Resultsmentioning
confidence: 55%
“…Before going on with the detailed discussion, we have to mention whether the excited state is delocalized over many or several D and A moieties in the crystals as an exciton or localized on one D−A pair. Hochstrasser et al and Haarer et al considered that CT excited states of molecular crystals of weak D−A complexes are rather localized (self-trapped), because of its alternating molecular stacks, strong electron−phonon coupling, and also an appreciable Coulomb interaction between generated highly ionic component molecules. , Recently, we compared the transient absorption spectrum of a 1:1 CT crystal of durene−PMDA and that of 10 -3 M PMDA-doped durene crystal and found good agreement between the spectra . Here, we have further diluted PMDA to 10 -4 M in the durene crystal, but its transient absorption spectrum was still in accordance with that of the 1:1 CT crystal.…”
Section: Resultsmentioning
confidence: 55%
“…Another origin of the self trapping of CT triplet excitons may be a distortion of the lattice upon excitation 24 . Such a distortion is expected if the equilibrium configurations in the excited state and in the ground state of the complex are different 25 . A simple distortion with a strong effect on the triplet energy would be a decrease in the interplanar distance.…”
Section: Comparison Of the Results In Row 3 And 4 Ofmentioning
confidence: 99%
“…The experiments of McGlynn and co-workers (251, 252) have been alluded to above. The phosphorescence of naphthalene, phenanthrene, and other hydrocarbons is reduced both in intensity and lifetime in complexes with 1,3,5-trinitrobenzene and other acceptors (54,55,56,153,247). Christodouleas and McGlynn (42) have found that complexing with trinitrobenzene increases the value of the ISC ratio by factors of 30 and 75 for naphthalene and acenaphthene, respectively.…”
Section: Phosphorescence Polarization In Heterocyclic Compoundsmentioning
confidence: 99%